Stellar Multiples Among the KOIs - Alyse Hirsch, Lea; Everett, Mark; Ciardi, David; Furlan, Elise; Horch, Elliott; Howell, Steve; Teske, Johanna; Marcy, Geoffrey W. (Bulletin of the American Astronomical Society, 2015)
We examine high-resolution follow-up imaging data for 84 KOIs with stellar companions detected within 2”. These stars were observed in the optical using speckle interferometry (Gemini/DSSI or WIYN/DSSI) and/or in the near-infrared with adaptive optics imaging (Keck/NIRC2, Palomar/PHARO, or Lick/IRCAL), and all have imaging results in at least two filters. Their companions are all unresolved in the Kepler images, and fall on the same pixel of the Kepler detector; thus the planet radii calculated for planet candidates in these systems are subject to upward revision due to contamination of the target star’s light by the stellar companion. We calculate updated planet radii for these 84 planet candidates, assuming the planet orbits the brighter of the two stars. We also use isochrone models and distance estimates to assess the likelihood that the companion is bound. This analysis complements galaxy models that determine the probability of a chance alignment of a background star for each system (Everett et al., in prep.). Together, these data allow us to isolate a sub-population of Kepler planets and planet candidates that reside in physical binary systems, for comparison to the wider Kepler planet population.
Conference Name: AAS/Division for Extreme Solar Systems Abstracts ADS Bibcode: 2015ESS.....311708A
Keywords: dept.phy; ⛔ No DOI found

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/163-960-215-288-558 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic